APLIKASI KLINIS PHOTOPAROXYSMAL RESPONSE - Donny Hamid*, Ridwan*, Gotot Sumantri* (Neurona Majalah Kedokteran Neuro Sains, 2010)
DIAGNOSIS OF PHOTOSENSITIVE EPILEPSY AS ANOTHER EPILEPSIES IN GENERAL IS MADE BY CLINICAL DESCRIPTION NOT BY EEG ONE TAKING HISTORY IN EPILEPSY PATIENT IS NOT ALWAYS EASY NO EYEWITNESS PATIENT COULD NOT REMEMBER HOW THE SEIZURES CAME IS ONE OF DIFFICULTY TO GET INFORMATION IN SEVERAL CASES